Comparison of tobacco and alcohol use in films produced in Europe, Latin America, and the United States. (December 2015) - Barrientos-Gutierrez, Inti; Kollath-Cattano, Christy; Mejía, Raul; Arillo-Santillán, Edna; Hanewinkel, Reiner; Morgenstern, Matthis; Sargent, James; Thrasher, James
Abstract Background Studies that have evaluated tobacco and alcohol portrayals in films have mainly focused on US films. Our aim is to describe tobacco and alcohol portrayals in nationally produced films from six European and two Latin American countries, and compare them with US produced films. Methods A sample of 337 nationally produced and 502 US produced films, consisting of top grossing films from 2004 to 2009 in each country, was content coded for presence of tobacco or alcohol and seconds of tobacco or alcohol use. Logistic and linear regression models were estimated for all films and youth-rated films (Ages 0–14) to assess cross country differences in tobacco and alcohol content, with US films as the reference category. Results Domestically produced films from several countries were more likely than US films to contain any tobacco use both overall (Iceland (OR = 9.29, CI: 1.22–70.89), Italy (OR = 3.58, CI: 1.72–7.43), Argentina (OR = 5.06, CI: 2.13–12.03), Mexico (OR = 4.87, CI: 2.17–10.90)) and for youth-rated films (Germany (OR = 2.24, CI: 1.21–4.16), Iceland (OR = 13.79, CI: 1.80–105.5), Italy (OR = 5.31, CI: 2.54–11.1), and Argentina (OR = 6.9, CI: 0.88–1.34)). Models for alcohol showed few differences compared to US, regardless of rating. Linear regression models for seconds of use in films with tobacco indicated that only Argentine films had more seconds of smoking than US films, regardless of the rating category. For films with alcohol use, Mexican films had higher seconds of alcohol use than US films. Conclusions Smoking was more commonly depicted in films produced outside the US, however there were few differences in the means for smoking screen time in films that contained smoking. This may be partly explained by the prohibition of tobacco product placement in the US. Countries should consider banning paid placement of both products and eliminating subsidies for films with content that promotes tobacco and alcohol use.